The Effect of the Project-Based Learning Model on Students’ Learning Outcomes in Pancasila Education for Fifth-Grade Students at SD Inpres 3 Talise - Oktafira Suciati; Arif Firmansyah; Muchdar Muchdar; Nashrullah Nashrullah; Mas'adi Mas'adi (FKIP - Universitas Riau, 2026)
This study aimed to determine the effect of the Project-Based Learning (PjBL) model on students’ learning outcomes in Pancasila Education for fifth-grade students at SD Inpres 3 Talise. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 47 students, including 24 students in the experimental class and 23 students in the control class. Data were collected through pretests and posttests administered before and after the learning intervention. The experimental class received instruction using the Project-Based Learning model, while the control class was taught using conventional learning methods. Data were analyzed using validity and reliability tests, normality tests, homogeneity tests, and the Mann–Whitney U test. The results showed that the average pretest score of the experimental class was 56.25 and increased to 84.16 in the posttest, while the control class improved from 54.87 to 70.21. The Mann–Whitney U test revealed a significance value of less than 0.05, indicating a significant effect of the Project-Based Learning model on students’ learning outcomes. Therefore, the Project-Based Learning model can be considered an effective and innovative learning approach for improving elementary school students’ learning outcomes in Pancasila Education.